Potential Health Benefits of Combining Yogurt and Fruits Based on Their Probiotic and Prebiotic Properties(1)(2)(3) - Fernandez, Melissa Anne (Adv Nutr, 2017)
Fruit and yogurt have been identified individually as indicators of healthy dietary patterns. Fruits are relatively low in energy density and are an excellent source of antioxidants and prebiotic fibers and polyphenols, which can promote digestive health. Yogurt, on the other hand, is a nutrient-dense food that is a good source of dairy protein, calcium, magnesium, vitamin B-12, conjugated linoleic acid, and other key fatty acids. In addition, it contains beneficial bacterial cultures, making it a potential source of probiotics. Yogurt’s unique fermented food matrix provides added health benefits by enhancing nutrient absorption and digestion. Combining the intake of yogurt and fruit could provide probiotics, prebiotics, high-quality protein, important fatty acids, and a mixture of vitamins and minerals that have the potential to exert synergistic effects on health. Yogurt consumption has been associated with reduced weight gain and a lower incidence of type 2 diabetes, whereas fruits have established effects on reducing the risk of cardiovascular disease. Yogurt and fruits can be eaten together and may exert combined health benefits through potential prebiotic and probiotic effects. Furthermore, substituting high-energy, nutrient-deficient snacks with fruit and yogurt could reduce the intake of high-calorie obesogenic foods. In light of the positive cardiometabolic impacts of fruit and yogurt and their association with healthy dietary patterns, there is sufficient evidence to warrant further exploration into the potential synergistic health benefits of a combined intake of fruit and yogurt.